Florida Cultivation Guide for Malabar Spinach - Yuheng Qiu; Guodong Liu (EDIS)
Malabar spinach (Basella spp.) is a nutritious vegetable in the family Basellaceae. Malabar spinach goes by many names, including Indian spinach, Ceylon spinach, vine spinach, and climbing spinach. Malabar spinach has long been established in cultivation in China and India. This spinach is a novel crop to Florida and is currently grown only for niche markets. However, Florida’s suitable climate coupled with Malabar spinach’s great taste and nutritional quality suggest that this crop has great potential for commercial cultivation. This new 8-page publication of the UF/IFAS Horticultural Sciences Department describes in brief how to grow Malabar spinach, manage pests, harvest, and market it. Written by Yuheng Qiu and Guodong Liu. https://edis.ifas.ufl.edu/hs1371